2015
DOI: 10.1186/s40064-015-1445-1
|View full text |Cite
|
Sign up to set email alerts
|

Pacing in a self-paced world record attempt in 24-h road cycling

Abstract: BackgroundPacing strategy plays a major role in sport performance. However, there is a dearth of knowledge concerning pacing during ultra-endurance sport events. The present case study investigated the pacing of an ultra-cyclist in a self-paced attempt to break the world record in 24-h road cycling and, with all the caveats and the limitations affecting a case report, could be useful in generating hypotheses and further studies about pacing dynamics during prolonged sport performances.Case descriptionA well ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Another parameter that might play a role on the performance in ‘Ultraman Hawaii’ is pacing. Although pacing has been studied extensively in separate endurance and ultra-endurance events ( Knechtle et al, 2015a ; Nikolaidis & Knechtle, 2016 ) and in shorter formats of triathlon ( Wu et al, 2016 ; Wu et al, 2015 ), no information on pacing in a multi-day triathlon such as ‘Ultraman Hawaii’ is available, i.e., how the performance in one event (e.g., swimming) influences the performance of subsequent events (e.g., cycling).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another parameter that might play a role on the performance in ‘Ultraman Hawaii’ is pacing. Although pacing has been studied extensively in separate endurance and ultra-endurance events ( Knechtle et al, 2015a ; Nikolaidis & Knechtle, 2016 ) and in shorter formats of triathlon ( Wu et al, 2016 ; Wu et al, 2015 ), no information on pacing in a multi-day triathlon such as ‘Ultraman Hawaii’ is available, i.e., how the performance in one event (e.g., swimming) influences the performance of subsequent events (e.g., cycling).…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that performance decreases during a multi-stage ultra-endurance triathlon ( Herbst et al, 2011 ; Knechtle et al, 2014 ). In race held over ten times the Ironman distance, performance progressively declined over days ( Knechtle et al, 2015a ; Knechtle et al, 2014 ). Additionally, sex has an influence on pacing during triathlon ( Le Meur et al, 2009 ; Vleck et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that environmental conditions such a wind and heat have an influence on ultra-endurance performance [62]. While it is known that wind has an influence on ultra-cycling performance [63], one might assume that also heat might impair ultra-endurance performance [64]. Triathletes competing under thermal stress conditions in the 'Ironman Hawaii' reached a state of hyperthermia during the marathon [65].It was observed that overall time was predictive for cycling performance of the following day and sleep time was not related to performance.…”
Section: Energy Expenditure Loss In Body Mass and Body Weight As Prementioning
confidence: 99%
“…Another parameter that might play a role on the performance in 'Ultraman Hawaii' is pacing. Although pacing has been studied extensively in separate endurance and ultra-endurance events (Knechtle et al 2015a;Nikolaidis & Knechtle 2016) and in shorter formats of triathlon (Wu et al 2016;Wu et al 2015), no information on pacing in a multi-day triathlon such as 'Ultraman Hawaii' is available , i.e. how the performance in one event (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that performance decreases during a multi-stage ultra-endurance triathlon (Herbst et al 2011;Knechtle et al 2014). In race held over ten times the Ironman distance, performance progressively declined over days (Knechtle et al 2015a;Knechtle et al 2014).…”
Section: Introductionmentioning
confidence: 99%